Hydrothermal Preparation of Ag/Ag1.69Sb2.27O6.25 Sesame-Hollow-Ball-Type Nanocomposites: The Formation Mechanism of Metallic Ag in the Ag-H2O System at 400 K - Haomei Liu; Xihai Hao; Yuejun Liu; Aiguo Yan (Advances in Materials Science and Engineering)
Ag/Ag1.69Sb2.27O6.25 sesame-hollow-ball-type nanocomposites were prepared via a facile one-step hydrothermal method at 400 K. Power X-ray diffraction analysis shows that all diffraction peaks were well consistent with JCPDS card no: 89-6552 of Ag1.69Sb2.27O6.25. Scanning electron microscopy and high-resolution transmission electron microscopy images of the composites indicate that some smaller metallic Ag particles with size∼18.3 nm uniformly dense on the surface of Ag1.69Sb2.27O6.25 hollow nanospheres with a mean size of about 170 nm, producing Ag/Ag1.69Sb2.27O6.25 hollow-sesame-ball nanocomposites. The surface chemical state of Ag/Ag1.69Sb2.27O6.25 is investigated by XPS, and all peaks of Ag 3d, O 1s, and Sb 3d show their different chemical states. The BET surface area of the sample is 7.268 m2/g, and the pore sizes of nanocomposites are more than 5 nm. The light absorption property of as-prepared materials is studied by UV-vis/DRS, and the adsorption band is located at 445 nm, and the estimated energy band gap (Eg) is 2.55 eV. The calculated partial φ-pH diagrams in the Ag-H2O system at 400 K predict that the Ag+ ion can react with H2 to form metallic Ag.